Encounters on contested lands : Indigenous performances of sovereignty and nationhood in Québec - Burelle, Julie (Performance works., 2019)
Encounters on Contested Lands analyzes films, plays, visual art, and protest marches by Indigenous artists in Quebec, Canada, to explore the performance of cultural identity, sovereignty, and nationhood in Quebec's independence movement--Provided by publisher.